Melancolia, capitalismo e laço social: uma leitura de Edvard Munch - Ferreira, Mariana Rodrigues Festucci (2016)
This dissertation proposes to think the condition of melancholy from aspects that define your way of structuring psychically and is located in the bonds and speeches, especially in speech capitalist, who prepare the enjoyment in contemporary society. For both, performs a qualitative research of interlocution between psychoanalysis and art, which unfolds in five stages:1. A history of the theorized about the melancholy of antiquity to modernity. 2. The melancholy in Freud, since their first approximations of the theme in the letters and drafts, who directs the then friend Fliess until the formalization conceptually undertaken in test Mourning and melancholy, not if I leave aside the additional considerations made in subsequent texts. 3. The Melancholy from theoretical considerations developed by Jacques Lacan regarding the constitution of the subject since the stadium of the mirror until the formalization of object a, passing by re-reading of Lacan testing of Freud in different moments of his teaching, his articulation of melancholy to pain to exist from Buddhism and culminating in the meeting of elements that allow to situate melancholy while clinical type of psychosis. 4. The relationship between melancholy, capitalism and social bond through the critique of the capitalist economic system operated by Benjamin, the theorizing of capitalist discourse as an offshoot of the discourse of the master proposed by Lacan, theorists who think the implications of this speech to the subjectivity of the subject in contemporary times without giving up the factors that count as the psychic structure, including Sidi Askofaré , Pacheco Filho and Vladimir Safatle, and joints to be made between the capitalist discourse and the outside-the-discourse of psychosis. 5. The reading of the melancholic expression, both regarding the psychic implications as social, in the work of painter Munch, aiming to take it as index of contemporary society. "Never will people understand that my paintings were created from seriousness and suffering" (Munch apud Tojner, 2004). It is concluded that such seriousness and suffering, however, served as an upholstery for him to go beyond his Art, marking how this way can act both in favor of the structural implications of the melancholic in the loop and the difficulties accentuated by the capitalist discourse. To this discourse Art, with its inventive potential, makes a hole, pointing out an alternative